Tradisi Intelektual Pesantren Raudatul Hasanah Modern di Kota Medan - Zakiah, Fauzana; Azhar, Ahmad; Hazmi, Deni; Dahlan, Zaini (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
One of the Islamic educational institutions that was present and then developed in Indonesia is the modern Raudatul Hasanah Islamic Boarding School in the city of Medan. In the early days of its existence, Islamic boarding schools were very synonymous with the study of religious sciences, making the Yellow Book a study material and learning reference. Therefore, in the dynamics of Islamic education in Indonesia, the yellow book does not only belong to Islamic boarding schools but has developed in other educational institutions, especially Islamic boarding schools. The method we use in this research is a descriptive-analysis research method with a qualitative approach, where the researcher will describe clearly the tradition of learning the yellow book in madrasas. Therefore, the main discussion in this article is to find out how the yellow book tradition exists in madrasas in Indonesia. In Islamic boarding schools in Indonesia, especially the modern Raudatul Hasanah Islamic boarding school in the city of Medan, apart from teaching aqliyah and lisâniyah sciences, they also pay great attention to the teaching of naqliyah sciences, namely sciences that come from the Koran and al-Hadith such as; Tafsir, Hadith, Fiqh, Tauhid, Sufism and so on, which are known as knowledge contained in the yellow books.